Superoxide Dismutase Administration: A Review of Proposed Human Uses - Arianna Carolina Rosa; Daniele Corsi; Niccolò Cavi; Natascia Bruni; Franco Dosio (Molecules, 2021)
Superoxide dismutases (SODs) are metalloenzymes that play a major role in antioxidant defense against oxidative stress in the body. SOD supplementation may therefore trigger the endogenous antioxidant machinery for the neutralization of free-radical excess and be used in a variety of pathological settings. This paper aimed to provide an extensive review of the possible uses of SODs in a range of pathological settings, as well as describe the current pitfalls and the delivery strategies that are in development to solve bioavailability issues. We carried out a PubMed query, using the keywords “SOD”, “SOD mimetics”, “SOD supplementation”, which included papers published in the English language, between 2012 and 2020, on the potential therapeutic applications of SODs, including detoxification strategies. As highlighted in this paper, it can be argued that the generic antioxidant effects of SODs are beneficial under all tested conditions, from ocular and cardiovascular diseases to neurodegenerative disorders and metabolic diseases, including diabetes and its complications and obesity. However, it must be underlined that clinical evidence for its efficacy is limited and consequently, this efficacy is currently far from being demonstrated.